1998
DOI: 10.1088/0026-1394/35/4/19
|View full text |Cite
|
Sign up to set email alerts
|

Absolute silicon photodiodes for 160 nm to 254 nm photons

Abstract: Silicon n-on-p photodiodes with 100 % internal quantum efficiency have been studied in the 160 nm to 254 nm spectral range. Preliminary values have been determined for the quantum yield of silicon at these wavelengths. Using these values, a trap detector is presented for absolute flux measurement in this region. The stability under intense 193 nm irradiation, a property of importance in lithography and in photorefractive keratectomy, has been measured, and the diodes tested were found to be several orders of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 13 publications
(15 reference statements)
0
43
1
3
Order By: Relevance
“…Recently, techniques, such as delta doping are proposed to make shallow junction. [24][25][26][27] The dead layer for mid-UV/far-UV absorption is still unavoidable. It was reported that the inversion-enhanced Si PN junction photodetector using fixed charges within oxide layer could alleviate the deadlayer problem, but the charges in oxide have stability issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, techniques, such as delta doping are proposed to make shallow junction. [24][25][26][27] The dead layer for mid-UV/far-UV absorption is still unavoidable. It was reported that the inversion-enhanced Si PN junction photodetector using fixed charges within oxide layer could alleviate the deadlayer problem, but the charges in oxide have stability issues.…”
Section: Introductionmentioning
confidence: 99%
“…At higher wavelengths or lower photon energies, the QY is approximately unity, and at wavelengths shorter than 360 nm 19 , this number is qualitatively proportional to the incident photon energies. This proportionality has been modeled and measured for higher photon energies including x-rays and has been reported for silicon by different groups as a constant number or as a function of incident photon energy [15,[19][20][21]. A detailed discussion can be found elsewhere [16,20,22].…”
Section: Resultsmentioning
confidence: 97%
“…For LYRA, two types of diamond detectors had been developed by IMOMEC (University of Limburg, Belgium): metal-semiconductormetal (MSM) photoconductors [8] and PIN (with the n-doped layer on top) photodiodes [9]. Si-AXUV photodiodes were selected as reference detectors [10] for comparison with the newly developed diamond devices. All LYRA detectors had been measured regarding their quantum efficiency, stability, response uniformity and linearity showing good radiometric characteristics under laboratory conditions [4].…”
Section: Onboard Detector Calibrationmentioning
confidence: 99%